Selective focus in reading: a social-based explanation - Braga, Denise B. (Lenguas Modernas, 2017)
Readers do not remember all the information presented in a text; the selection of information has been considered a by-product of the reading process in general. The present investigation regards it as a product of one of the processes involved in reading, i.e. selective focus. The existing literature analyzes selective focus within the framework of two perspectives: reader-based and text-based. This paper reviews this literature and considers the possibility of a third perspective based on social factors, a perspective which is discussed in the light of some recent studies and illustrated by the findings of Braga (1990). Finally, the work addresses the implications of a social based conception of selective focus for the teaching of reading.